Indirect evidentiality in Dutch and German: a contrastive corpus study of the seem-type verbs schijnen and scheinen - Mortelmans, Tanja (Kalbotyra, 2017)
The present study deals with the seem-type verbs schijnen and scheinen in Dutch and German. On the basis of an in-depth analysis of spoken and written corpus material, the construction types these verbs typically appear in as well as their function and meaning are analysed. As seem-type verbs often develop into evidential markers (this is the case in e.g. English, French and Spanish), I will particularly concentrate on evidential uses (and the syntactic patterns that are associated with those uses). The study will lay bare important differences between German, Belgian Dutch and Netherlandic Dutch regarding both verbs. Moreover, the distinction between spoken and written language will be shown to play a crucial role with respect to the construction types found. Finally, the fact that the verbs exhibit different constructional preferences will be linked to different semantic properties as well.